Handbook of compound semiconductors : growth, processing, characterization, and devices - Holloway, Paul H.; McGuire, G. E. (Materials science and process technology series. Electronic materials and process technology., 1995)
This book reviews the advances and technologies used to produce microelectronic and optoelectronic devices from compound semiconductors. It provides an overview of the technologies necessary to grow bulk single-crystal substrates, grow hetero-or homoepitaxial films, and process advanced devices such as HBT's, QW diode lasers, etc.